2021
DOI: 10.34133/2021/9806173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of COVID-19 Guideline Quality and Change of Recommendations: A Systematic Review

Abstract: Background. Hundreds of coronavirus disease 2019 (COVID-19) clinical practice guidelines (CPGs) and expert consensus statements have been developed and published since the outbreak of the epidemic. However, these CPGs are of widely variable quality. So, this review is aimed at systematically evaluating the methodological and reporting qualities of COVID-19 CPGs, exploring factors that may influence their quality, and analyzing the change of recommendations in CPGs with evidence published. Methods. We searched … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The number is close to the number of clinical practice guidelines of COVID-19. [16] The majority of these guidelines were published in peer-reviewed journals in English by developers from high-income countries such as Canada and the United States. There is a lack of guidelines for COVID-19 vaccines from low- and middle-income countries and published in languages other than English and a lack of recommendations for these countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number is close to the number of clinical practice guidelines of COVID-19. [16] The majority of these guidelines were published in peer-reviewed journals in English by developers from high-income countries such as Canada and the United States. There is a lack of guidelines for COVID-19 vaccines from low- and middle-income countries and published in languages other than English and a lack of recommendations for these countries.…”
Section: Discussionmentioning
confidence: 99%
“… [7] To address this problem, practice guidelines have been developed by many organizations and institutions aiming to translate the research findings into recommendations for practice and to provide a guidance for the appropriate use of COVID-19 vaccination. [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] There are already many different types of guidelines at present, some of the guidelines are brief, others lengthy, however, the overall picture of the vaccine guidelines is unclear. To our knowledge so far, no study has comprehensively summarized the characteristics of these guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential improvement to guidance document development is a prospective register which could reduce duplication and foster greater collaboration. 18 This study demonstrates that while the general quality of guidelines in anaesthesia is recognized as poor, the guidance documents produced during COVID-19 offered an even lower standard, despite readily available aids such as appraisal tools. Based on the findings of this study, a suggested ideal COVID-19 guidance document in anaesthesia would utilise an appraisal tool during development, take a collaborative approach with multi-institutional and international involvement and adhere to the requirements of AGREE II, particularly Domains 1,3,4 and 6.…”
Section: Discussionmentioning
confidence: 86%
“…16 This has been amplified during the COVID-19 era due to lack of an existing evidence base, purported absence of rigour in some guideline development strategies, use of non-standard document formats, and use of confusing terminology. 17 , 18 Several publications have detailed the quality of anaesthesia guidelines and the quality of COVID-19 recommendations in other fields of medicine. 15 , 17 , 19 One small anaesthesia study offered an early indication as to the standard of COVID-19 guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the COVID-19 outbreak, close to 100 international and national clinical practice guidelines (CPGs) for the management of adult COVID-19 patients have been developed [ 3 ]. However, there are so far only few evidence-based guidelines specifically focusing on pediatric COVID-19 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%